Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex](m+2)(m+3)=(m+2)(m-2)\\\\m^2+3m+2m+6=m^2-4\\\\m^2-m^2+5m=-4-6\\\\5m=-10\ \ \ \ /:5\\\\m=-2[/tex]
The first time you look at this, you would think that you can just cancel the
(m+2) off of each side. But then you're left with (m+3) = (m-2), and there's
no solution for this. So you have to go back and do it the hard way.
Expand each side of the equation. (Clear the parentheses.)
m² + 5m + 6 = m² - 4
Subtract m² from each side:
5m + 6 = -4
Subtract 6 from each side:
5m = -10
Divide each side by 5:
m = -2
(m+2) off of each side. But then you're left with (m+3) = (m-2), and there's
no solution for this. So you have to go back and do it the hard way.
Expand each side of the equation. (Clear the parentheses.)
m² + 5m + 6 = m² - 4
Subtract m² from each side:
5m + 6 = -4
Subtract 6 from each side:
5m = -10
Divide each side by 5:
m = -2
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.